2021
DOI: 10.1101/2021.01.22.427431
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Human genetic analyses of organelles highlight the nucleus in age-related trait heritability

Abstract: Aging is associated with defects in many organelles, but an open question is whether the inherited risk for age-related disease is enriched within loci relevant to each organelle. Here, we begin with a focus on mitochondria, as mitochondrial dysfunction is a hallmark of age-related disease. We report a striking lack of enrichment of mitochondria-relevant loci across GWAS for 24 age-related traits. Analyses of nine additional organelles reveal enrichment only for the nucleus, particularly nuclear transcription … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 140 publications
0
7
0
Order By: Relevance
“…For instance, TFs are strongly enriched for haploinsufficient disease associations, resulting from the loss of one functional allele and ∼50% dosage reduction, and are depleted of loss-of-function (LoF) variants in the general population 7, 8 . Genome-wide association studies have revealed thousands of trait-associated common variants, many of which likely act by modulating RE activity and target gene expression levels 9, 10 ; trait-associated variants are also highly enriched around TF genes 11, 12 . Both experimental and population-level data generally suggest per-allele effects of up to 10-15% 13, 14 , which may be even smaller for important, dosage-sensitive genes such as TFs.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, TFs are strongly enriched for haploinsufficient disease associations, resulting from the loss of one functional allele and ∼50% dosage reduction, and are depleted of loss-of-function (LoF) variants in the general population 7, 8 . Genome-wide association studies have revealed thousands of trait-associated common variants, many of which likely act by modulating RE activity and target gene expression levels 9, 10 ; trait-associated variants are also highly enriched around TF genes 11, 12 . Both experimental and population-level data generally suggest per-allele effects of up to 10-15% 13, 14 , which may be even smaller for important, dosage-sensitive genes such as TFs.…”
Section: Introductionmentioning
confidence: 99%
“…We next tested mtCN corr for heritability enrichment in genes associated with organelles or organs using stratified LD-score regression (S-LDSC, Finucane et al, 2015, 2018; Gupta et al, 2021), Methods ). Encouragingly, the most significant organelle enrichment was seen for the mitochondrion ( Supplementary figure 4C ).…”
Section: Resultsmentioning
confidence: 99%
“…Published mtscATACseq data used for chrM:302 analysis can be obtained via approval from dbGaP. Gene-sets for enrichment analyses can be obtained using COMPARTMENTS (https://compartments.jensenlab.org) and MitoCarta 2.0 (https://www.broadinstitute.org/files/shared/metabolism/mitocarta/human.mitocarta2.0.html) as described previously (Gupta et al, 2021). The GRCh37 and GRCh38 reference genomes as well as other standard reference data are available via the GATK resource bundle: https://gatk.broadinstitute.org/hc/en-us/articles/360035890811-Resource-bundle.…”
Section: Data Availabilitymentioning
confidence: 99%
“…The majority of candidate gene studies have been underpowered for the effect size being reported, questioning the strength of the original findings, which often did not incorporate well-known nuclear genetic risk loci in the same analyses. Although mitochondrial genes have fallen within high risk loci mapped for common disorders in hypothesis-free genome-wide association studies (as for ATP5G1 in type 2 diabetes) 79 , a recent meta-analysis found no evidence of enrichment for mitochondrial genes in genome-wide association data for 24 age-related human traits 80 . There are therefore no convincing validated examples of specific nuclear alleles associated with common diseases within known mitochondrial genes.…”
Section: Role Of Common Nuclear Genomic Variants In Common Diseasesmentioning
confidence: 99%
“…This is, perhaps, surprising given the previous arguments made in this review. However, functional redundancy of essential metabolic pathways and the semi-autonomous nature of mitochondria are potential explanations 80 .…”
Section: Role Of Common Nuclear Genomic Variants In Common Diseasesmentioning
confidence: 99%